(untitled) (ENTHYMEMA, 2025)
Building upon the rich theoretical framework that Derrida conceives in his posthumous environmental reflections and the interdiscipline of biosemiotics, this essay delves into the ethical questions posed by Stephen King related to other-than-human sentience, suffering, and subjecthood in “Rat.” Derrida and King generate thought-provoking portrayals of what happens when we are confronted with the gaze of the “wholly other.” When the other-than-human gaze falls upon us, Derrida and King insist that we cannot disregard the ethical summons that accompanies it. This transformative gaze compels us to think and live otherwise. The limitrophic reflection actuated by the other-than-human gaze eliminates the sharp ontological gap between humans and other animals. Owing to the strength of these encounters with other-than-human alterity, species boundaries erected on the shaky foundation of binary logic become unclear and unstable. The epiphany that the biosphere is replete with other semiotic agents that are capable of conceiving, transmitting, and decoding signs further erodes the pervasive doctrine of human exceptionalism.